2007
DOI: 10.1073/pnas.0611631104
|View full text |Cite
|
Sign up to set email alerts
|

Reduced expression of mitochondrial frataxin in mice exacerbates diet-induced obesity

Abstract: Published evidence suggests that adiposity in humans may be linked to impaired energy expenditure for reasons widely unresolved. We have generated mice with a systemic impairment of oxidative phosphorylation (OXPHOS) due to aP2 cre-mediated targeted disruption, and unexpectedly ubiquitous reduction of mitochondrial frataxin protein expression. Only when maintained on a high-calorie diet resembling Westernized eating habits, these animals accumulate additional body fat, leading to increased body mass, and devel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(18 citation statements)
references
References 49 publications
0
15
0
3
Order By: Relevance
“…Mitochondrial dysfunction could result in cellular disruptions that could be related to complications associated with obesity via modifications of lipid metabolism and energy partitioning. Mice with systemic impairment of oxidative phosphorylation are more sensitive to obesity and to diabetes mellitus than control mice when fed a high-calorie diet under the same conditions of energy intake and physical activity (33). In humans, it has been shown that oxidative phosphorylation genes are also down-regulated in white adipose tissue of morbidly obese subjects compared with lean subjects, whereas after surgery-induced weight loss, an up-regulation of these genes was observed (34).…”
Section: Discussionmentioning
confidence: 98%
“…Mitochondrial dysfunction could result in cellular disruptions that could be related to complications associated with obesity via modifications of lipid metabolism and energy partitioning. Mice with systemic impairment of oxidative phosphorylation are more sensitive to obesity and to diabetes mellitus than control mice when fed a high-calorie diet under the same conditions of energy intake and physical activity (33). In humans, it has been shown that oxidative phosphorylation genes are also down-regulated in white adipose tissue of morbidly obese subjects compared with lean subjects, whereas after surgery-induced weight loss, an up-regulation of these genes was observed (34).…”
Section: Discussionmentioning
confidence: 98%
“…O aumento de peso e tecido adiposo pode ser resultado da alteração na modulação hipotalâmica da sinalização da leptina em função da hiperleptinemia. Além disso, redução da massa e capacidade oxidativa mitocondrial também podem ser observadas em roedores alimentados com dieta hiperlipídica, favorecendo maior acúmulo de gordura (11,12).…”
Section: Discussionunclassified
“…Some studies indicate that impairment on mitochondrial metabolism may lead to excessive body weight gain when the subjects are fed with high-calorie western diets 44. The study of Townsend et al45 offered two different diets (hyperlipidic and hypolipidic) to rats, both diets predominant in saturated fat.…”
Section: Obesity-inducing Factorsmentioning
confidence: 99%